2020
DOI: 10.1590/1516-3180.2019.0459.r1.19112019
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Bloom’s taxonomy, judges’ estimation of item difficulty and psychometric properties of items from a progress test: a prospective observational study

Abstract: BACKGROUND: Progress tests are longitudinal assessments of students' knowledge based on successive tests. Calibration of the test difficulty is challenging, especially because of the tendency of item-writers to overestimate students' performance. The relationships between the levels of Bloom's taxonomy, the ability of test judges to predict the difficulty of test items and the real psychometric properties of test items have been insufficiently studied. OBJECTIVE: To investigate the psychometric properties of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
(38 reference statements)
0
9
0
4
Order By: Relevance
“…Due to considerable overlap between boundaries, low numbers of ‘Apply’ questions and no questions from levels 4–6 of Bloom’s taxonomy, we combined ‘Understand’ and ‘Apply’ questions to produce a binary predictor of ‘Remember’ versus ‘Understand/Apply’. We recognize that some evidence suggests no linear relationship between taxonomic level and item difficulty (Cunnington et al, 1996 ; Hamamoto Filho et al, 2020 ) and there is limited evidence to support Bloom’s taxonomy as a single, linear hierarchy in this way (Furst, 1981 ; Haladyna & Rodriguez, 2013 ; Marzano & Kendall, 2007 ). However, our main hypothesis was that factual recall questions would be made selectively easier in an OBE, so we considered collapsing the categories appropriate to compare, in effect, recall questions versus questions that required more than recall.…”
Section: Methodsmentioning
confidence: 89%
“…Due to considerable overlap between boundaries, low numbers of ‘Apply’ questions and no questions from levels 4–6 of Bloom’s taxonomy, we combined ‘Understand’ and ‘Apply’ questions to produce a binary predictor of ‘Remember’ versus ‘Understand/Apply’. We recognize that some evidence suggests no linear relationship between taxonomic level and item difficulty (Cunnington et al, 1996 ; Hamamoto Filho et al, 2020 ) and there is limited evidence to support Bloom’s taxonomy as a single, linear hierarchy in this way (Furst, 1981 ; Haladyna & Rodriguez, 2013 ; Marzano & Kendall, 2007 ). However, our main hypothesis was that factual recall questions would be made selectively easier in an OBE, so we considered collapsing the categories appropriate to compare, in effect, recall questions versus questions that required more than recall.…”
Section: Methodsmentioning
confidence: 89%
“…Recently, it was reported that question items with high-level taxonomy performed better in discrimination indices. [30] Ideal questions reached only 32% yet higher levels were reported in literature 47% [31].…”
Section: Discussionmentioning
confidence: 98%
“…Items are multiple choice questions with four options and a single correct answer. Preferably, the items are clinical vignette-based aiming for applied knowledge rather than knowledge recall [25]. In 2019, four existing consortia in São Paulo state developed the exam by selecting the best pre-tested items (tested between 2013 and 2018 and preferably, between 2016 and 2018, with good discrimination indices) conforming to the commonly used blueprint.…”
Section: Progress Testmentioning
confidence: 99%
“…In this regard, the philosophy of the new curriculum (i.e., more integration between the basic sciences and social sciences applicable to medicine) may support the performance of students in basic sciences and public health. Notably, students exposed to the new curriculum integrating basic and clinical sciences may be better prepared for the interinstitutional Progress Test [31], which uses high taxonomy vignette-based items [25]. In addition, experiences in community settings may also contribute to early medical education [32].…”
Section: Plos Onementioning
confidence: 99%